2005
DOI: 10.1103/physrevb.72.054412
|View full text |Cite
|
Sign up to set email alerts
|

Crystal and magnetic structure ofCa3Ru2O7

Abstract: The crystal structure of the double-layered Ca 3 Ru 2 O 7 has been studied by convergent beam electron diffraction and powder neutron diffraction. The temperature dependence of the diffraction pattern reveals that all the lattice constants jump at the first-order metal-nonmetal transition at 48 K without a change of the space group symmetry of Bb2 1 m. In the neutron diffraction experiment, an additional magnetic reflection emerges below the Néel temperature, 56 K. A possible model for this antiferromagnetic o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
158
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(171 citation statements)
references
References 17 publications
13
158
0
Order By: Relevance
“…24 Below the spin-flop transition field B c , the probed AFM structure is consistent with the model previously proposed for Ca 3 Ru 2 O 7 by DFT calculations 23 and powder neutron diffraction studies, 14 i.e. FM bilayers, with magnetic moments oriented along the b-axis, are stacked antiferromagnetically along the c-axis (This phase was labeled AFM-b in Ref.…”
Section: Introductionsupporting
confidence: 67%
See 2 more Smart Citations
“…24 Below the spin-flop transition field B c , the probed AFM structure is consistent with the model previously proposed for Ca 3 Ru 2 O 7 by DFT calculations 23 and powder neutron diffraction studies, 14 i.e. FM bilayers, with magnetic moments oriented along the b-axis, are stacked antiferromagnetically along the c-axis (This phase was labeled AFM-b in Ref.…”
Section: Introductionsupporting
confidence: 67%
“…Such a switch of magnetic easy-axis across the AFM-a/AFM-b phase boundary was initially identified in magnetization measurements by Cao et al, 12 and later confirmed by neutron scattering measurements. 14,24 Neutron scattering studies have also revealed that the giant/colossal magnetoresistance originates from the spin flop transition from the AFM-b to CAFM phase 24 . This indicates that interlayer spin scattering dominates electronic transport properties in Ca 3 Ru 2 O 7 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A tilt already necessarily exists for the c axis-aligned moments in the canted AF phase, and the strong spin-lattice coupling in perovskite iridates 17 supports the notion of an accompanying structural tilt. Such a tilt likely renders Sr-327 isostructural to Ca 3 Ru 2 O 7 (space group: Bb2 1 m) 18 ; however, a full neutron data set and structural refinement have yet to be carried out.…”
Section: Resultsmentioning
confidence: 99%
“…The rare observations of ferromagnetism in insulating transition-metal oxides most often are due to a particular type of orbital ordering [2]. The few examples of antiferromagnetic (AFM) metals, e.g., (La/Sr) 3 Mn 2 O 7 [3] or Ca 3 Ru 2 O 7 [4], are characterized by reduced electronic and structural dimensionality, and the antiferromagnetic order corresponds to a stacking of ferromagnetic (FM) layers. Here we report the discovery of a three-dimensional transition-metal oxide with metallic conductivity, antiferromagnetic exchange interactions, and C-type antiferromagnetic order: the perovskite CaCrO 3 .…”
mentioning
confidence: 99%